2010
DOI: 10.1038/ja.2010.36
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory activity of blasticidin A, a strong aflatoxin production inhibitor, on protein synthesis of yeast: selective inhibition of aflatoxin production by protein synthesis inhibitors

Abstract: Blasticidin A (BcA), an antibiotic produced by Streptomyces, inhibits aflatoxin production without strong growth inhibition toward aflatoxin-producing fungi. During the course of our study on the mode of action of BcA by two-dimensional differential gel electrophoresis (2D-DIGE), we found a decrease in the abundances of ribosomal proteins in Saccharomyces cerevisiae after exposure to BcA. This phenomenon was also observed by treatment with blasticidin S (BcS) or cycloheximide. BcA inhibited protein synthesis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 23 publications
(17 reference statements)
1
26
0
Order By: Relevance
“…Aspergillus parasiticus NRRL 2999 was used as a producer of aflatoxins B 1 and G 1 throughout the study [19]. Aflatoxins B 1 and G 1 are the main aflatoxins produced by the NRRL 2999 strain.…”
Section: Methodsmentioning
confidence: 99%
“…Aspergillus parasiticus NRRL 2999 was used as a producer of aflatoxins B 1 and G 1 throughout the study [19]. Aflatoxins B 1 and G 1 are the main aflatoxins produced by the NRRL 2999 strain.…”
Section: Methodsmentioning
confidence: 99%
“…It is a potent inhibitor of AF biosynthesis by A. parasiticus (Sakuda et al, 2000). Using two-dimensional differential gel electrophoresis (2D-DIGE) Yoshinari et al (2010) showed that blasticidin A inhibited AF (total of B 1 and G 1 ) production and fungal growth with IC 50 values of 0.25 and 1.6 µM, respectively. MALDI-TOF MS analysis of protein spots on the 2D-DIGE gel of blasticidin A-treated A. flavus showed decreased amounts of AF biosynthetic enzymes including Vbs, OmtB, OmtA, NorA, Ver-1 and Nor-1 after 36 h treatment.…”
Section: Blasticidins a And S From Streptomyces Griseochromogenesmentioning
confidence: 99%
“…Precocene II may affect a regulatory mechanism leading to expression of TRI6 in the trichothecene production pathway in the fungus. To investigate the mode of action of precocene II, proteome analysis by two-dimensional differential gel electrophoresis (2D-DIGE) was performed [14,15]. …”
Section: Resultsmentioning
confidence: 99%